ANALISIS EFEKTIVITAS SELF-MANAGEMENT SUPPORT TERHADAP KUALITAS HIDUP PASIEN KANKER PAYUDARA - Adelina Sembiring; Lisdayanti Simanjuntak; Lisbet Gurning; Sri Mulati Nendah Agreta; Petra Diansari Zega; Abdul Mazid Bancin (Ensiklopedia Research and Community Service Review, 2026)
Breast cancer and its treatments impose a complex symptom burden that negatively affects patients’ quality of life. Self-management support (SMS) is a patient empowerment strategy aimed at enhancing independence in nursing care. This study aimed to analyze the effectiveness of SMS on the quality of life of breast cancer patients at Haji General Hospital Medan. Methods: This study employed a quasi-experimental design with a pre–post test control group approach. The sample consisted of 60 respondents (30 in the intervention group and 30 in the control group), selected using purposive sampling. The intervention group received structured education and self-monitoring guidance for 8 weeks. The research instrument used was the EORTC QLQ-C30 questionnaire. Data were analyzed using Paired T-test and Independent T-test. Results: There was a significant increase in the mean quality of life score in the intervention group, from 52.3 to 75.6 (p 0.001), while the control group showed no significant change (p = 0.125). Intergroup comparison after the intervention revealed a statistically significant difference (p = 0.000). The emotional functioning and pain management domains showed the most substantial improvements. Conclusion: Self-management support is effective in improving the quality of life of breast cancer patients. This intervention is recommended to be integrated into standard oncology nursing care to promote patient independence in managing treatment-related side effects. Keywords: Breast Cancer, Quality of Life, Self-Management Support, Medical-Surgical Nursing.